Governance Mechanisms and Bond Prices - K. J. Martijn Cremers; Nair, Vinay B.; Chenyang Wei (Review of Financial Studies, 2007)
[We investigate the effects of shareholder governance mechanisms on bondholders and document two new findings. First, the impact of shareholder control (proxied by large institutional blockholders) on credit risk depends on takeover vulnerability. Shareholder control is associated with higher (lower) yields if the firm is exposed to (protected from) takeovers. In the presence of shareholder control, the difference in bond yields due to differences in takeover vulnerability can be as high as 66 basis points. Second, event risk covenants reduce the credit risk associated with strong shareholder governance. Therefore, without bond covenants, shareholder governance, and bondholder interests diverge.]